1979
DOI: 10.1002/1097-0142(197908)44:2<457::aid-cncr2820440212>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Remission of giant lymph node hyperplasia with anemia after radiotherapy

Abstract: We have described a 51-year-old patient with unresectable mesenteric giant lymph node hyperplasia of the plasma cell type, severe systemic manifestations, and profound anemia. Supression of erythropoiesis may have been related to the presence of a circulating erythropoietic inhibitor produced by the lymphoid tumor. Markedly elevated titers to Epstein-Barr virus capsid antigen suggest that this virus may be important in the etiology of the abnormal lymphoid proliferation. The marked clinical response and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Low dose radiotherapy (2700 -4500 cGy) administered to involved sites has been reported to result in remission of disease in isolated cases 33,[42][43][44][45][46][47][48][49] but has failed in others. 3,8,51 Keller et al 3 reported on four patients with unicentric-HV disease who were treated with 1800 -4300 cGy with no response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low dose radiotherapy (2700 -4500 cGy) administered to involved sites has been reported to result in remission of disease in isolated cases 33,[42][43][44][45][46][47][48][49] but has failed in others. 3,8,51 Keller et al 3 reported on four patients with unicentric-HV disease who were treated with 1800 -4300 cGy with no response.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation was noted to produce a range of favorable responses in all patients with unicentric disease of PC or mixed histology. 42,45,46,49,50 Perhaps the most intriguing therapeutic problem is the treatment of multicentric disease with radiotherapy in which the bulk of all known disease must be incorporated in a radiation field. 4 We report a complete, lasting remission (Ͼ1 year) in 1 patient with multicentric HV-CD treated with 3960 cGy.…”
Section: Discussionmentioning
confidence: 99%
“…The condition has many synonyms, including angiomatous lymphoid hamartoma2 and giant lymph node hyperplasia of the mediastinum.3 The aetiology is unknown, but is presumed to be infectious or inflammatory, and the lymph node lesions always behave as benign tumours. 4 Keller, Hochholzer and Castleman3 analysed 81 cases and divided the lesions into two types: the hyaline-vascular-in which systemic complications are not usually observed-and the plasma cell variant, which is frequently accompanied by fever, anaemia and hyperglobulinaemia. In the latter type, complete surgical resection of the tumour is followed by resolution of all the systemic manifestations.…”
mentioning
confidence: 99%
“…Radiotherapy is used in those patients with incomplete excision or unresectable lesions, but its effectiveness is limited [41]. Steroid and aggressive systemic chemotherapy are recommended for treatment of the severe multicentric form of Castleman's disease [36,37].…”
Section: Discussionmentioning
confidence: 99%